Artists Unsettling Anthropocentrism: Review of Giovanni Aloi, Speculative Taxidermy: Natural History, Animal Surfaces, and Art in the Anthropocene - Turner, Stephanie (Humanimalia, 2021)
Giovanni Aloi, Speculative Taxidermy: Natural History, Animal Surfaces, and Art in the Anthropocene. New York: Columbia University Press, 2018. 315 pp. $30.